Bile Acid-Activated Receptors, Intestinal Microbiota, and the Treatment of Metabolic Disorders. Issue 11 (November 2015) - Fiorucci, Stefano; Distrutti, Eleonora
Abstract : The composition of the bile acid pool is a function of the microbial metabolism of bile acids in the intestine. Perturbations of the microbiota shape the bile acid pool and modulate the activity of bile acid-activated receptors (BARs) even beyond the gastrointestinal tract, triggering various metabolic axes and altering host metabolism. Bile acids, in turn, can also regulate the composition of the gut microbiome at the highest taxonomic levels. Primary bile acids from the host are preferential ligands for the farnesoid X receptor (FXR), while secondary bile acids from the microbiota are ligands for G-protein-coupled bile acid receptor 1 (GPBAR1). In this review, we examine the role of bile acid signaling in the regulation of intestinal microbiota and how changes in bile acid composition affect human metabolism. Bile acids may offer novel therapeutic modalities in inflammation, obesity, and diabetes. Trends: Bile acids are synthesized in the liver as primary bile acids, cholic (CA) acid and chenodeoxycholic acid (CDCA), and are transformed by the intestinal microbiota into a variety of metabolically active metabolites, including secondary bile acids, deoxycholic and lithocholic acids (DCA and LCA). Primary and secondary bile acids are signaling molecules acting as agonists or antagonists on a family of nuclear (FXR) and G-protein-coupled (GPBAR1) receptors, collectively known as bile acid-activated receptors (BARs). Manipulation of intestinal microbiota by probiotics and bariatric surgeries alters bile acid metabolism, reshaping FXR and GPBAR1 signaling. FXR and GPBAR1 agonists modulate insulin signaling, increase energy expenditure, and alleviate liver lipid accumulation Targeting FXR and GPBAR1 signaling by specific agonists and/or antagonists, probiotics and/or diet components is a promising approach for the treatment of metabolic disorders, diabetes, and obesity.